Nutrition : a lifespan approach - Langley-Evans, S. C. (Wiley-Blackwell, 2009)
Traditionally, nutrition textbooks have divided human nutrition into basic science, public health and clinical nutrition, however in this exciting new textbook, Professor Simon Langley-Evans spans these divisions, bringing together the full range of disciplines into one accessible book through the lifespan approach.